KAJIAN TATA KELOLA PEMERINTAHAN BERBASIS TEKNOLOGI KOMUNIKASI DALAM MEWUJUDKAN REVOLUSI 4.0 DI KABUPATEN KONAWE SELATAN - Liwaul, Liwaul; Taufik, Taufik; Nur, Muhammad Nadzirin; Lestari, Indra (Jurnal Ilmiah Penyuluhan dan Pengembangan Masyarakat, 2023)
Evaluation of the implementation of SPBE in several regional governments in Southeast Sulawesi Province shows that achievements are not very good. Based on the results of the SPBE evaluation of several regional governments in Southeast Sulawesi Province, it shows that the South Konawe Regency Government is in first place with the predicate "Sufficient" and has an index of 2.52. This research aims to determine information and communication technology-based governance in the South Konawe Regency Government and the factors that influence it. This research was carried out at the South Konawe Regency Regional Government. In this research, there are four Regional Apparatus Organizations (OPD) and one Village Government which are designated as units of analysis. This research uses descriptive research with a qualitative research approach. Data collection techniques used in this research include: interviews, observation and documentation. The data analysis technique that researchers use refers to interactive model analysis according to Miles and Huberman which is carried out in 3 flows, namely; carry out data reduction, present data (data display), and draw conclusions. The research results show that the application of information and communication technology supports the realization of good governance in the South Konawe Regency Government. This can be seen from the various digital service application innovations that have been developed which are capable of creating government governance that is responsive, effective, efficient, and has perceived benefits and impacts. Although it has not yet optimally utilized the role of ICT in terms of information transparency and public accountability in aspects of regional budget management performance. The establishment of a vision and goal to become a Smart City has triggered the South Konawe Regency Government and all Regional Apparatus Organizations (OPD) to be very enthusiastic in developing and implementing an electronic-based government system (SPBE). The Regent's visionary leadership towards digital-based governance reform is a determining factor in the success of e-government development in South Konawe Regency. Leadership with a clear vision and strong commitment to e-government plays an important role in efforts to provide all the resources needed such as institutions (policies and regulations, institutional strengthening), human resources, budgets and digital/ICT infrastructure.